AUDIT AND CORPORATE CHARACTERISTICS AFFECTING AUDIT REPORT LAG: EVIDENCE FROM INDONESIAN STOCK EXCHANGE CONSUMER CYCLICALS (2022-2024) - Martha Angelina Manalu; Kurniawati (Sampoerna University, 2026)
Audit report lag (ARL) among consumer cyclicals sector issuers on the Indonesia Stock Exchange (IDX) throughout the 2022–2024 period is evaluated in this study based on agency and signaling theories. This research applies a quantitative methodology, relying on a secondary database of audited annual financial statements. To filter the population, purposive sampling criteria were implemented to finalize a sample of 100 corporations, encompassing 300 total firm-year observations. All data were tested using a multiple linear regression model via EViews 14 software. The empirical estimations reveal that company scale has a significant negative effect on the duration of the audit process. Conversely, the dimensions of key audit matters disclosure, profitability levels, and public accounting firm reputation demonstrate no substantial statistical contribution to explaining this reporting lag. Consequently, the asset capacity of an entity emerges as a critical aspect capable of influencing audit duration and accelerating the publication of financial information to the market.